Penggunaan Teknik Discrete Trial Training dalam Meningkatkan Kemampuan Mengenal Warna Siswa Autis di SLB Paulus Tomohon - Henny B.A Kiriweno (Peneliti.net, 2021)
This research began with the discovery of autistic children at the Paul Tomohon Special School who did not know primary colors. The use of learning media without using techniques is not enough to support the development of the ability to recognize primary colors in children. Efforts to overcome these problems are carried out by using the discrete trial training (DTT) technique, which is one of the handling approaches in the field of education that is closely related to experience, direct involvement and spontaneity. The formulation of the problem in this study: can the use of discrete trial training techniques improve the ability to recognize primary colors in autistic children at SLB Paulus Tomohon? This study aims to find out the use of discrete trial training techniques can improve the ability to recognize primary colors, and can improve the quality of learning at SLB Paulus Tomohon. The type of research method used in this study is single subject research (SSR), with an A-B-A research design. Data analysis at baseline (A1) was 5 sessions long with a mean level of 0.6, the percentage of stability was 0%. Furthermore, at the intervention stage (B) the length of the condition was 10 sessions with a mean level of 10.5 and a percentage of 50% stability. The baseline stage (A2) with a condition length of 5 sessions and a mean level of 14, the percentage of stability is 100%. The overlap data obtained between conditions B/A1 and A2/A1 is 0%, thus there is no overlapping data. The results of this study indicate that the discrete trial training (DTT) technique has an effect on increasing the ability to recognize primary colors in autistic children in the preparatory class at SLB Paulus Tomohon. It is recommended that the discrete trial training (DTT) technique can be used as one of the learning media in the classroom to help children improve their ability to recognize basic colors.